Spain, a country without picture books ? - Mauclair, Patricia (Ondina - Ondine, 2023)
In this paper, we will see that even if the notion “classic” in children’s literature is still being debated in Spain,  it still marginalizes picture books and picture book series. They are apparently still not worthy of being considered «classics» of spanish literature.Key words : picture book, Spain, classic book, picture books series.